Evaluacion de dos parasitoides de huevos de Nezara viridula - Catalan, J.=700 1 Verdu, M.J.
(En, Es)
ilus., 18 ref.
Keywords: CAPSICUM; NEZARA VIRIDULA; PARASITOIDES; TRIáSOLCUS; OOENCYRTUS; CONTROL BIOLOGICO; ESPAÑA